Consumed by influence: the role of social media in shaping maternal identity and product choices during complementary feeding - Ozturk, Pelin; Kaya, Cigdem (Frontiers in Communication, 2025)
IntroductionIn today’s digital age, social media platforms radically transform consumption practices and identity construction. This study examines the impact of influencers’ product recommendations on Instagram on mothers’ product preferences during the complementary feeding period. The research reveals that consumption practices shaped by influencer guidance are based on symbolic and social identity motivations and functional needs.MethodsThe study used a mixed-methods approach, surveying 711 mothers in Türkiye with children aged 6-48 months. Quantitative data were analyzed statistically, while open-ended responses were thematically analyzed to explore symbolic meanings and consumption patterns.ResultsInfluencer-following mothers showed a stronger tendency to prioritize peer recommendations and branded BLW products. Items purchased based on influencer suggestions were often linked to social approval, visibility, and the construction of a modern parenting identity. However, over 80% of participants later expressed disappointment, citing issues of limited functionality or questionable necessity. Additionally, age-based differences emerged in both motivations for following influencer recommendations and post-purchase evaluations.DiscussionThe findings indicate that influencer-promoted products serve as symbols of modern, conscious motherhood but often fail to meet practical expectations. Influencer culture fosters FoMO, driving mothers toward social approval and intensifying emotional labor. While younger mothers engage with influencer content as part of a digital habitus, older mothers use it for symbolic inclusion. Notably, mothers aged 40+ and 18-29 reported similar levels of satisfaction, suggesting that their relationships with influencers were different yet equally impactful.